Open and Closed Reduction for Developmental Dysplasia of the Hip in New York State: Incidence of Hip Reduction and Rates of Subsequent Surgery. Issue 1 (January 2020) - Swarup, Ishaan; Ge, Yile; Scher, David; Sink, Ernest; Widmann, Roger; Dodwell, Emily
Abstract : Background: There are limited data on the incidence and outcomes of open and closed hip reduction in patients with developmental dysplasia of the hip (DDH). The aims of this study were to determine the incidence of open and closed reduction of the hip using population-level data and to assess the rates of subsequent surgery. Methods: Children aged 3 years and younger with DDH who underwent open or closed reduction of the hip between 1997 and 2013 were identified in the New York Statewide Planning and Research Cooperative System (SPARCS) database. Patient age, sex, race, and insurance status as well as concurrent procedures were extracted. Admissions through 2014 were searched for subsequent surgeries, providing a minimum 1-year post-reduction surveillance for all patients. Age-specific incidence rates were calculated using New York State annual population data. The rates of concurrent and subsequent surgeries were calculated. A sensitivity analysis was performed to provide a range for the rates of subsequent surgery. Univariate analyses consisted of chi-square or Fisher exact tests for categorical variables. Results: In total, 897 patients (637 who underwent closed reduction and 260 who underwent open reduction) were identified. The age-specific incidence per 100, 000 population was 12.5 for closed reduction and 2.6 for open reduction for <1-year-olds, 2.2 for both closed and open reductions for 1-year-olds, 0.4 for closed reduction and 1.0 for open reduction for 2-year-olds, and <0.3 for closed reduction and 0.5 for open reduction for 3-year-olds. Overall, closed reductions were performed more frequently over the study period (p < 0.01). The estimated rate of subsequent ipsilateral surgery was 12.4% (range, 9.4% to 33.1%) after index closed reduction and was 14.2% (range, 8.5% to 40.1%) after index open reduction. Conclusions: We found that the incidence of closed or open hip reduction for DDH was small and that there was an increase in the number of closed reductions performed over time. The rates of subsequent surgery remained relatively high for patients after index closed or open hip reduction. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.